Case on Lease Accounting of a multinational telecommunication company (Robi Axiata limited, Bangladesh) - Mahmud, Jawad (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.